Progress in the development of human parainfluenza virus vaccines. (August 2011) - Schmidt, Alexander C; Schaap-Nutt, Anne; Bartlett, Emmalene J; Schomacker, Henrick; Boonyaratanakornkit, Jim; Karron, Ruth A; Collins, Peter L
In children under 5 years of age, human parainfluenza viruses (HPIVs) as a group are the second most common etiology of acute respiratory illness leading to hospitalization, surpassed only by respiratory syncytial virus but ahead of influenza viruses. Using reverse genetics systems for HPIV serotypes 1, 2 and 3 (HPIV1, 2 and 3), several live-attenuated HPIVs have been generated and evaluated as intranasal vaccines in adults and in children. Two vaccines against HPIV3 were found to be well tolerated, infectious and immunogenic in Phase I trials in HPIV3-seronegative infants and children and should progress to proof-of-concept trials. Vaccines against HPIV1 and HPIV2 are less advanced and have just entered pediatric trials.